Overcome the Difficulty of Understanding Shalat With the Demonstration Method - Dea Kamelia; Imam Tabroni; Devilia Agisti; Marwah Mu'minah (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
The purpose of this study is to analyze how important it is the application of the demonstration method in Islamic religious learning education material for 3rd grade prayer at Al-Ma'ruf Elementary School. The type of research method used is qualitative. The research subjects are tutors, and class teachers and school students. The object of the research is the application of the demonstration method of learning material for the 3rd grade Duha prayer at SD Al-Ma'ruf. The results showed that the application of the demonstration method is good enough to be applied in learning materials for prayer. Using the demonstration method in learning issued by the teacher to demonstrate directly the prayer movement material to students in sequence students can accept and follow what the teacher does properly and correctly. The use of demonstration methods is important to be applied in education Islamic learning in prayer material because students' attention can be focused on participating in learning activities, the learning process of learning by students is more focused.